Penerapan Strategi Pemasaran dalam Upaya Meningkatkan Penjualan Menggunakan Metode SOAR dan QSPM pada Studi Kasus Thrift Store Labersa Pekanbaru - Handika, Puri Tri; Lubis, Fitriani Surayya; Hartati, Misra; Umam, Muhammad Isnaini Hadiyul; Nazaruddin, Nazaruddin (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The purpose of this study was to help solve problems related to factors that influence reduced income or sales achievement using the SOAR and QSPM methods. The purpose of using the SOAR and QSPM matrices is to find valid and practical results for the problems faced by the owner of the Thrift shop Labersa Pekanbaru. The method used in this study is qualitative where researchers obtain research results through distributing questionnaires with primary data types, namely direct interviews with the owner and related parties, while the method in the research data uses the SOAR and QSPM methods as a reference in concluding the results of the questionnaire. The results of the study found that the results of the validity and reliability tests said valid and reliable, then the results of the IE and SOAR matrix analysis quadrants were obtained in quadrant V with the aim that the store in that phase must maintain the market and develop products. The final results of the SOAR and QSPM tests obtained AS and TAS 6.758 are the highest results by providing pre-order services for branded goods according to customer demand and exclusive shopping fields.